IMAGINING SWEETER AUSTRALIA-INDONESIA RELATIONS - John Blaxland (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
Australia’s relationship with Indonesia has been a bit like the board game “Snakes and Ladders”. Incremental progress in the relationship (up the ladder) is easily undone (down the snake) over a range of misunderstandings including issues like beef, boats, spies, clemency, Timor and Papua. Both countries have considerable overlapping interests. They both have to find a way to deepen and broaden the bilateral relationship to prevent this cycle from continuing to recur. In considering how to do that, understanding how they got here is important. Bilateral and multilateral engagement, on trade, education, and security including through IA-CEPA, links like the Ikahan network, additional New Colombo Plan engagement and a MANIS regional maritime cooperation forum may help make that happen.